Gendered Entrepreneurship Networks - Simen Markussen; Knut Røed (Institute for the Study of Labor (IZA), 2016)
In virtually all industrialized countries, women are underrepresented in entrepreneurship, and the gender gap exhibits a remarkable persistence. We examine one particular source of persistence, namely the prevalence of gendered networks and associated peer effects. We study how early career entrepreneurship is affected by existing entrepreneurship among neighbors, family members, and recent schoolmates. Based on an instrumental variables strategy, we identify strong peer effects. While men are more influenced by other men, women are more influenced by other women. We estimate that differences between male and female peer groups explain approximately half of the gender gap in early career entrepreneurship.
Keywords: L26; M13; J16; 330; early career entrepreneurship; peer effects; gender gap; instrumental variables